2020
DOI: 10.1001/jamapsychiatry.2020.2159
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Neuropsychiatric Copy Number Variants in a Health Care System Population

Abstract: IMPORTANCE Population screening for medically relevant genomic variants that cause diseases such as hereditary cancer and cardiovascular disorders is increasing to facilitate early disease detection or prevention. Neuropsychiatric disorders (NPDs) are common, complex disorders with clear genetic causes; yet, access to genetic diagnosis is limited. We explored whether inclusion of NPD in population-based genomic screening programs is warranted by assessing 3 key factors: prevalence, penetrance, and personal uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 84 publications
3
64
0
Order By: Relevance
“…Furthermore, EHR access also enables correlation of clinically relevant results with personal and family history of disease leading to more informed clinical care. Lastly, implementation of population genomic screening in an integrated, learning healthcare system allows longitudinal analyses of outcomes data and can inform future guidance on the personal, medical, and financial utility of such programs (Buchanan et al, 2020; Haggerty et al, 2017; Hao et al, 2020; Jones et al, 2018; Patel et al, 2019; Savatt et al, 2020) and facilitate expansion beyond what most programs are reporting at this time (Martin et al, 2020; Savatt et al, 2020).…”
Section: Challenges and Benefits Encounteredmentioning
confidence: 99%
“…Furthermore, EHR access also enables correlation of clinically relevant results with personal and family history of disease leading to more informed clinical care. Lastly, implementation of population genomic screening in an integrated, learning healthcare system allows longitudinal analyses of outcomes data and can inform future guidance on the personal, medical, and financial utility of such programs (Buchanan et al, 2020; Haggerty et al, 2017; Hao et al, 2020; Jones et al, 2018; Patel et al, 2019; Savatt et al, 2020) and facilitate expansion beyond what most programs are reporting at this time (Martin et al, 2020; Savatt et al, 2020).…”
Section: Challenges and Benefits Encounteredmentioning
confidence: 99%
“…CNVs can be analyzed from different biological sources, offering various valuable information, so there are plenty of biomedical applications where CNV detection may be useful. CNVs have been studied in neuropsychiatric [72,73], developmental [74], and cardiovascular diseases [75]. Several studies have identified the role of CNVs in common diseases such as coronary artery disease or in rarer events such as sudden cardiac death.…”
Section: Potential Biomedical Applications Of Cnv Detectionmentioning
confidence: 99%
“…Recordings were transcribed verbatim. A grounded theory approach with two independent coders (KW and KT) was used to develop an initial codebook using the first 14 transcripts [15,23]. The remaining 13 transcripts were similarly coded independently and discussed to assess for thematic saturation and to refine the final codebook.…”
Section: Qualitative Analysis Of Audio-recorded In-person Genetic Counseling Sessionsmentioning
confidence: 99%
“…NPD represent an etiologically heterogenous group of clinically defined disorders, including autism spectrum disorder, intellectual disability, epilepsy, schizophrenia, bipolar disorder, and others [ 14 , 15 ]. These disorders are collectively common, affecting at least 14–18% of children and adults in the United States [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation